Etika Profesi Bimbingan dan Konseling: Konseling Kelompok Online dan Asas Kerahasiaan - Diana Syamila; Happy Karlina Marjo (Universitas Pendidikan Mandalika, 2022)
The purpose of this study was to discuss the ethical role of the guidance and counseling profession, especially the principle of confidentiality in the implementation of online counseling. This research method uses a descriptive qualitative literature review that examines several scientific articles accompanied by the results of interviews and previous research results. The data analysis technique uses descriptive analysis techniques. The results of this study explain that counselors have an ethical responsibility to explain the meaning of confidentiality in group counseling. The principle of confidentiality is important considering that the professional ethics of the counselor pays more attention to the privacy of the counselee, because it will involve comfort and security in receiving counseling services. In the implementation of online counseling, counselors can anticipate the possibility of unwanted violations by making efforts such as: (1) Conducting interviews and evaluations when forming groups, (2) Conducting in-depth observations when providing classical services in the classroom, (3) Grouping individuals who voluntarily and voluntarily participate in group activities, (4) Giving informed consent containing personal data, applicable rules, and cooperation agreements which contain the privacy security of themselves and other members, (5) Members affix their signatures on the under a statement about what they will accept if they do not fulfill it.